PERUBAHAN POLA INISIASI PRIMORDIA SELAMA PEMBUNGAAN: KAJIAN LITERATUR MEKANISME TRANSISI MERISTEM VEGETATIF KE REPRODUKTIF - Nisa Aulia; Wan Syafi'i (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Flowering is an essential phase in the plant life cycle, influencing reproductive success and overall productivity. One of the earliest indicators of flowering is the formation of floral primordia, which emerge due to physiological changes and environmental influences. This literature review analyzes patterns of primordium initiation during the transition from vegetative to reproductive meristems by utilizing recent publications from the last five years. The meristem transition is influenced by interactions among genetic regulation, plant hormones, and environmental factors such as photoperiod, temperature, and nutrient availability. Floral primordium formation progresses through several morphological stages marked by changes in shoot apical meristem activity. The review highlights the significant roles of flowering regulatory genes and gibberellin hormones in initiating primordia. The findings offer deeper insights into flowering mechanisms and serve as a foundation for future research in plant physiology and breeding.